PENGARUH BIAYA PROMOSI DAN TARIF KAMAR TERHADAP PENDAPATAN HOTEL NOVILLA BOUTIQUE & RESORT, SUNGAILIAT BANGKA (Studi Kasus Pada Hotel Novilla, Sungailiat Periode 2014-2018) - Elvira Mano, Paula; Oktalina, Gayatria; Ruben Manullang, Rizal (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This study aimed to determine the effect (1) promotion costs and simultaneously room rates for hotel revenue (2) promotion expenses partially on hotel revenue and room rates to earnings in hotel and (3) partially room rater to earnings in hotel. This study uses a quantitative research design causal. The subjects were peace hotel NovillaSungailiat and its object is the promotion expenses, room rates and revenues in 2014 – 2018. The type of data in this research is kuantitative data, the data is collected by recording the interview documentation and analyzed by multiple linear regression analysis with t-test, F-test and coefficient of determination (R2) use (JASP 0,9,2,0Universiteit-Van-Amsterdam). The result showed that there is a (1) simultaneous influence of the cost of promotion and room rates to hotel revenue where F-count > F-table (20,902 > 19,00) with sign 0,046 > 0,05. The influence of the partial cost of promotion (2) have positive and sign t-count > t-table with absolute value (5.876 > 3,18245) and significant 0,028 < 0,05, meaning H0 is rejected and H1 accepted. While the variable of room rates (3) no influenceof partial on rates to revenue t-hitung< t-tabel (-1,892 < 3,18245) with sign.0,199 > 0,05. Meaning H0 accepted H2 is rejected. For R2 test obtained R square 0,769% means 76,9% hotel revenue is influenced by both variables. While the remaining 23,1% influenced by other variables that are not influded in this study.